HP43: Electrophysiological reactions to intraoperative irritation of the optic nerve: A clue for intraoperative optic nerve mapping?. (March 2022) - Levin, E.; Kiselev, R.; Vasyatkina, A.; Semin, P.
Abstract : Intraoperative control of optic nerve function preservation during neurosurgical operations currently relies mainly on monitoring of visual evoked potentials. Unfortunately, they detect peril only when the visual pathways are already compromised, sometimes irreversibly. In contrast, electrophysiological stimulation mapping of the nerves can be a fully preventive measure. However, direct sensory nerve mapping requires the patient to be awake during surgery, which is hardly feasible for surgeries targeting the optic nerve area. Another possible approach to sensory nerve mapping involves unconditioned electrophysiological responses evoked by sensory nerve stimulation. The necessary prerequisites for this approach are existence and stability of such responses for a particular sensory nerve in conditions of surgical anesthesia. Case report . A 52-year-old woman presented with meningioma in the area of right optic nerve and chiasm. She underwent microsurgical removal of the tumor through a transciliary supraorbital approach. Total intravenous anesthesia with propofol was used throughout the surgery. During the surgery, electrodes at the inferior margin of the right orbit repeatedly recorded electrophysiological reactions following touches, tractions and releases of tractions of the right optic nerve by the surgical instruments. Conclusions . The observed reactions suggest that either the unconditioned blink reflex or antidromic electroretinographic response to optic nerve irritation was conserved under the total intravenous anesthesia. This observation might be of value for development of intraoperative optic nerve mapping. This in turn could increase patients safety by identifying the optic nerve location without negative impacts on it. This report is accepted for publication in the Neurochirurgie journal: https://doi.org/10.1016/j.neuchi.2021.03.014.